Effects of calcium application on apple fruit softening during storage revealed by proteomics and phosphoproteomics - Xu, Yaxiu; Liu, Jiaojiao; Zang, Nannan; Yin, Zepeng; Wang, Aide (Horticultural plant journal, 2022)
Fruit ripening has been reported to be related to calcium (Ca), but the underlying mechanisms by which Ca regulates this process remain largely unknown. In order to study the changes of proteins and enriched phosphopeptides, we conducted TMT labeling, bio-material-based PTM enrichment based on mass spectrometry in Ca-treated ‘Golden Delicious’ (GD) apple fruit (Malus. × domestica). This dataset presents a comprehensive overview of the critical pathways involved in fruit ripening. A total of 47 proteins and 124 phosphoproteins significantly changed in Ca-treated fruit, which are crucial for regulating the cell wall and cytoskeleton, Ca-mediated signaling and transport, ethylene production, protein fate, especially ubiquitination-based protein degradation, and primary and secondary metabolisms. Our results indicated that Ca inhibited the abundance of polygalacturonase (PG) activity and increased the phosphorylation level of CSLD3. PG and phosphorylation were involved in cell wall degradation, thereby delaying fruit softening As a secondary messenger, Ca-mediated signaling subsequently triggered downstream mitogen-activated protein kinases (MAPK) cascades and activated the membrane, transport, and ROS signaling. Moreover, MdEIN2, a key enzyme involved in the ubiquitin of protein modification, increased at Ser753 and Ser758 in Ca-treated fruit. Furthermore, diverse primary and secondary metabolisms including glycolysis, fatty acid metabolism, and oxidation respiratory chain were modulated to prevent fruit softening. These results provide basic information from protein and phosphorylation levels for apple fruit ripening during storage, which may be helpful for apple fruit storage control.